Aesthetic Experience and Global Competence: a museum-inspired online course. Issue 3 (2nd July 2020) - Hubard, Olga
Abstract: This article presents Aesthetic Experience and Global Competence, a graduate-level online course for educators in all areas, whose development was rooted in art museum education practices. The article includes details on the course, which was built around a series of group inquiries into works of art and literature related to a broad topic: "movement and displacement." Following these inquiries, students explored their own experiences of movement and displacement through the creation of a digital photomontage and a piece of creative writing. By the end of the course, students came to understand the significance of art experiences to global competence around six interrelated themes: (a) Feeling others' experience, sharing humanity, (b) gaining fluency in and valuing different ways of knowing, (c) considering multiple perspectives, (d) nurturing self-awareness about one's situation, (e) dwelling in ambiguity, and (f) motivation to continue to learn about global issues and different ways of life. The implications of students' responses to art museum education are discussed.